A list of the fleas (Siphonaptera) of Mexico with new host and distribution records - Salceda-Sánchez, Beatriz; Hastriter, Michael W. (Zootaxa, 2006)
A total of 163 species (including subspecies) of fleas represented by 51 genera, are documented in the Republic of Mexico. Nineteen new records from ten states and six new host records are reported. Orchopeas intermedius Hubbard and Stenoponia americana (Baker) are recorded for the first time in the country. Fifty per cent (16) of the 32 states in Mexico have 11 or fewer published records. Euhoplopsyllus glacialis affinis (Baker), collected in 1945, is the only flea species known from the state of Aguascalientes.